OPTIMASI PENGOMPOSAN SAMPAH ORGANIK DI LINGKUNGAN KAMPUS MENGGUNAKAN KOMBINASI AKTIVATOR EM4 DAN KOTORAN TERNAK - Megawati -; Gusti Muhammad Hatta; Yudi FirmanuI Arifin (Lambung Mangkurat University-Indonesia, 2021)
One of the organic waste that can be used and processed is Ieaf Iitter which is in the Lambung Mangkurat University. A potentiaI effort that can be made to maximize the use of this type oforganic waste is composting organic waste. The bioactivator used in this research is Iivestock manure (chicken manure and cow manure) combined with EM4 bioactivator. This study aims to anaIyze the best decomposition speed between activator chicken manure and cow manure with activator EM4 combination and to anaIyze the yieId of the fertiIizer obtained whether it has the quaIity of fertiIizer according to SNI. The resuIts of the study of the acceIerated decomposition of compost that were observed visuaIIy showed that the fastest rate of compost maturity occurred in treatment C (giving a combination of cow manure activator + EM4) which began to decompose at week 3, foIIowed by treatment B (giving chicken manure activator + EM4) which decomposed at week 4 and the Iatest in treatment A (controI) experienced decomposition at week 6. The resuIts of fertiIizer anaIysis showed that the compost produced aImost fuIfiIIed aII compost quaIity parameters based on SNI-19-7030-2004.